Model pengelolaan perpustakaan Pondok Pesantren As’adiyah Sengkang kab. Wajo Provinsi Sulawesi Selatan - Irvan Mulyadi (Literatify: Trends in Library Developments, 2023)
The management model of a madrasah library can serve as a reference for other madrasah libraries to ensure that their libraries can effectively fulfill their duties and functions as a source of learning for students. This research aims to uncover a library management model that includes the development of a strategic plan, collection management, and library services development at the As'Adiyah Sengkang Islamic boarding school, which is a middle-level Islamic education institution that has produced many prominent scholars and intellectuals. A total of 27 pages of interview transcripts from various library managers who volunteered as informants in this study were analyzed through qualitative research stages. The research results indicate that: The boarding school's planning meetings provide a platform for librarians to present their strategic plans, The library's vision serves as a reference for librarians in formulating their strategic plans, Purchases and alumni donations are techniques used for collection development, Textbooks and fiction books are the priorities for librarians to acquire, Love for books, service commitment, mutual understanding, and mutual respect among staffs are the fundamental principles followed by librarians in carrying out their duties. This research is limited to only Islamic boarding school libraries of As’Adiyah Sengkang and may not represent a comprehensive model for madrasah library management as a whole.